CONOCIMIENTO Y PREVENCIÓN DE ANEMIA FERROPÉNICA EN MADRES DE NIÑOS MENORES DE 3 AÑOS DE LA ASOCIACIÓN DUNAS DE VILLA-PISCO 2021 - Sarita Saturno Fabian (2022)
The present research aimed to determine the relationship between the knowledge and prevention of iron deficiency anemia in mothers of children under 3 years of age of the Dunes Association of Villa-Pisco 2021. Presenting a methodology of basic type, being its design non-experimental, descriptive correlational. The population was made up of 125 mothers and the sample was made up of 94 mothers of children under 3 years of age of the Dunes Association of Villa-Pisco 2021; as a technique, the survey was used, with two questionnaires being the instruments used for data collection. The results showed that 15.96% present a knowledge at a low level, 55.32% a medium level and 28.72% a high level. Likewise, it was found that 15.96% present a prevention of iron deficiency anemia at a bad level, 54.26% a regular level and 29.79% a good level. Therefore, it was concluded that there is a significant relationship between the knowledge and prevention of iron deficiency anemia in mothers of children under 3 years of age of the Dunes Association of Villa-Pisco 2021, according to Spearman's correlation of 0.723 this relationship is direct and positive with a statistical significance of p = 0.000 being less than 0.01. Keywords: Knowledge, prevention of anemia, iron deficiency anemi